Relationship between body mass index and the clinical predictors of polycystic ovary syndrome in adolescent girls - Somayeh Abdolahian; Fahimeh Ramezani Tehrani; Fatemeh Nahidi; Delaram Ghodsi; Mahdi Jafari; Hamid Alavi Majd (Mashhad University of Medical Sciences, 2021)
Introduction: Polycystic ovary syndrome is one of the most common endocrine diseases of adolescents in the world, which has negative effects on fertility issues in adulthood. Since adolescent weight gain increases the risk of symptoms, this study was performed with aim to investigate the relationship between adolescent body mass index and clinical predicting factors of polycystic ovary syndrome. Methods: This descriptive- analytical study was conducted in 2019 on 751 adolescents aged 16 to 18 years at risk of polycystic ovary syndrome in Tehran girls' high school. Body mass index, menstrual cycle, hair loss, acne and hirsutism were examined. Data were analyzed by SPSS software (version 25) and chi-square and logistic regression tests. P<0.05 was considered statistically significant. Results: The results of the showed that there was no significant relationship between body mass index with menstrual cycle order (p = 0.142) and also acne (p = 0.64). But significant positive relationship was found between body mass index with hirsutism (p = 0.02) and also hair loss (p = 0.03). Conclusion: The increase in body mass index is associated with increase in the severity of clinical symptoms of hyperandrogenism such as hair loss and hirsutism in female adolescents at risk for polycystic ovary syndrome.